Synthesis Pharmacological Evaluation, Molecular Docking And Cytotoxicty Studies On Some N-Substituted 5-[(4-Chlorophenoxy)Methyl]-1,3,4-Oxadiazole-2yl-2-Sulfanyl Acetamides - Siddiqui, Sabahat Zahra; Abbasi, Muhammad Athar; Rehman, Aziz-ur; Irshad, Misbah; Shahzad, Babar; Mohd Ashraf, Ahmad; Ahmad, Irshad; Lodhi, Muhammad A.; Mirza, Bushra; Ismail, Hammad; Akhtar, Muhammad Nadeem (IndianScience.in, 2014)
The framework of our systematic efforts focuses on the synthesis of N-substituted 5-[(4-chlorophenoxy) methyl]-1,3,4-oxadiazole-2yl-2-sulfanyl acetamides. 4-Chlorophenoxyacetic acid (1) was utilized as a precursor for the synthesis of parent 1,3,4-oxadiazole moiety. Esterification of 1in the presence of catalytic amount of concentrated sulfuric acid and absolute alcohol generated ethyl 2-(4-chlorophenoxy)acetate (2) which was treated with hydrazine hydrate to yield 2-(4-chlorophenoxy)acetohydrazide (3). Ring closure reaction of 3 with carbon disulfide and alcoholic potassium hydroxide afforded [5-(4-chlorophenoxy)methyl)]-1,3,4-oxadiazole-2-thiol (4). Finally, substitution at thiol position of 4 with electrophiles, N-substituted-2-bromoacetamides (6a-p) in polar aprotic solvent and LiH yielded various N-substituted 5-[(4-chlorophenoxy) methyl]-1,3,4-oxadiazole-2yl-2-sulfanyl acetamides (7a-p). IR, 1H-NMR and EI-MS spectral analysis data unequivocally confirmed all the substitutions on 1,3,4-oxadiazole-2-thiol core. It was recognized that the synthesized derivatives are potential anti-bacterial agents against both gram negative and gram positive bacteria and moderate inhibitors of α-chymotrypsin enzyme. In vitro screening against various bacterial strains unleashed their anti-bacterial potential, especially 5-[(4-chlorophenoxy)methyl]-1,3,4-oxadiazol-2yl-N-(3,4-dimethylphenyl)-2-sulfanyl acetamide (7o) exhibited marvelous activity when compared with standard ciprofloxacin against S.typhi (-), K.pneumonae (-) and S. aureus (+).Compounds were computationally docked with the α-chymotrypsin enzyme protein to unravel the active binding sites which displayed significant correlation with the bioactivity data. It can be envisioned that the amalgamation of 5-[(4-chlorophenoxy)methyl]-1,3,4-oxadiazole-2-thiol with N-substituted-2-bromoacetamides generated N-substituted 5-[(4-chlorophenoxy)methyl]-1,3,4-oxadiazole-2yl-2-sulfanyl acetamides having tremendous antibacterial activity and moderate anti-enzymatic potential. Moreover, substitutions on the oxadiazole moiety lead to the discovery of less cytotoxic compounds as evident from the cytotoxicity data.